Hardy’s existentialist approach to life with reference to his major novels - Saima Manzoor; Fouzia Rehman Khan; Durdana Khoso (The Journal of Humanities & Social Sciences, 2022)
Hardy has a multidimensional approach to the work of art. His philosophy is concerned with the nature of existence and individual‟s freedom of action and its consequences. His art is the reflection of his realistic approach, marked with sympathy and empathy, to life in general and his innate association with his indigenous land. He holds human actions and passions responsible for producing dire consequences.